PEMBUATAN PETA TEMATIK PENYEBARAN PROFESIONAL PEREKAM MEDIS DAN INFORMASI KESEHATAN BERBASIS SISTEM INFORMASI GEOGRAFIS (SIG) BERDASARKAN LETAK WILAYAH KERJA DI PROVINSI RIAU TAHUN 2017 - Haryani Octaria, Sy. Effi Daniati, Nur Maimun, Zulhendry (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Making thematic maps of professional dissemination of PMIK is one of the effective andefficient ways to analyze and visualize data and information, it will be easier for PORMIKIRiau DPD or local government to present more interesting and active information.Because the data is put in the form of maps, and it is very easy to read and understand itfor the local government in making a decision in its Settlement, PMIK in every healthservice facility in the district / city of Riau Province. The purpose of this study is to provideinformation relevant to available data (GIS). The research method used is descriptivequalitative. This research was conducted medically and information about health in RiauProvince in 2016 was 197 people. Data analysis conducted in this study was spatialanalysis (Reclassify). The results of the study show that the distribution of professionalmedical recorders and health information (PMIK) based on the work area of 12 regencies/ cities in Riau province stood 294 people spread out unevenly where the highestdistribution was Medical Recorder and Health Information (PMIK) districts in pekanbarucity It is located in 176 people, while the Professional Distribution of Medical Recordersand Health Information (PMIK), which has a small area in the archipelago, is one of thepeople in the Meranti archipelago which is not included in the Riau provincial province ofthe Riau archipelago.Keywords: Making Thematic Maps, Medical Recorders and Health Information Basedon Geographic Information Systems (GIS)